Autonomic computing for exception management in supply chains ( part 2 ) - Foo, Wei Shing. (2010)
This project investigates how continuous and discrete control theory may be applied to model, monitor and control a supply chain based on performance indicators such as rapid inventory recovery and order rate recovery.